The Religious Harmony Tolerance in Indonesia: An Islamic Perspective of Pluralism and Multiculturalism - Wahidah, Evita Yuliatul; Sirait, Sangkot; Kusumaputri, Erika Setyanti (Proceedings of Annual Conference for Muslim Scholars, 2022)
The academic problems in this study are researching the problem complexity about a value system that present positive and optimistic view on the plurality of religions, cultures, customs, and even interaction pattern by accepting them as a real reality and kindness. Based on the context of religious harmony tolerance phenomenon without having personal theological distortion experience in order to keep the strong spiritualism by correlating the studies of pluralism and multiculturalism in Islamic perspective. It is a literature qualitative research with documentary review and data analysis which uses three activity plots that occur simultaneously, which consists of data reduction, data presentation, conclusion drawing or verification. This study explores the conceptualization of religious harmony between western and Islamic perspectives, the history of religious harmony tolerance in Indonesia, the basics of religious harmony tolerance, the pluralism essence in the context of religious harmony, and last is examining about multiculturalism in the perspective of religious harmony.